Factors that influence the choice of long-acting reversible contraceptive use among adolescents post-abortion in Chongqing, China: a cross-sectional study - Fengzhen Jin; Yuanpei Yang; Junjie Sun; Ruiyue Li; Fei Yao; Xiaoli Liu (Journal of Obstetrics and Gynaecology)
Background Induced abortion can seriously harm the physical and mental health of adolescent women. Long-acting reversible contraception (LARC) can effectively reduce unplanned pregnancies and prevent repeated abortions among adolescents. This study aimed to analyse the factors affecting the choice of LARC among adolescents in Chongqing of China.Methods A total of 555 adolescents who underwent induced abortions for unplanned pregnancies between January 2019 and October 2021 were selected as study subjects. Logistic regression analysis was used to determine the factors affecting adolescent LARC choices following induced abortions.Results The factors that affected adolescent LARC choices included an average monthly income ≥ ¥3000 (OR = 3.432, 95% CI: 1.429∼8.244), history of previous abortions (OR = 3.141, 95% CI: 1.632∼6.045), worrying about unplanned pregnancy (OR = 0.365, 95% CI: 0.180∼0.740), parental support for using LARC (OR = 3.549, 95% CI: 1.607∼7.839), sexual partners’ support for using LARC (OR = 2.349, 95% CI: 1.068∼5.167), concerns about using LARC (OR = 0.362, 95% CI: 0.176∼0.745), and willingness to use free IUDs (OR = 13.582, 95% CI: 7.173∼25.717).Conclusion Cost is one of the factors affecting LARC choices. Parents and sexual partners may play important role in the choice of LARC.